Deteccion de fitoplasmas en frutales mediante la reaccion en cadena de la polimerasa (PCR) - Avinent, L.=700 1 Llacer, G.
(Es, En)
ilus., 14 ref.
Keywords: BACTERIOSIS; MYCOPLASMA; PCR; ARBOLES FRUTALES; ALBARICOQUE; CIRUELA; MANZANA; PERA; ESPAÑA; FITOPLASMA